2021
DOI: 10.3947/ic.2021.0010
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsions with Chloroaluminium Phthalocyanine and Paromomycin for Combined Photodynamic and Antibiotic Therapy for Cutaneous Leishmaniasis

Abstract: Background Photodynamic therapy (PDT) using chloroaluminium phthalocyanine (ClAlPc) and paromomycin sulfate (PM) can be effective against New World Leishmania species involved in cutaneous leishmaniasis (CL). The aim of this study is to assay the skin permeation and the antileishmanial effects of a nanoemulsion (NE) containing both ClAlPc and PM in experimental CL by Leishmania (Viannia) braziliensis . Material and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It is important to highlight that each species of Leish mania presents specific biochemical and molecular characteristics, and their sensitivity to drugs is different [25]. Published studies reported the in vivo efficacy of treatments with FEX and ClAlPc against different species that cause leishmaniasis, such as L. donovani, L infantum, L. amazonensis, and L. braziliensis, showing promising results [5][6][7]13,15,26] However, until now, no study has been found that evaluated the effectiveness of thes treatments against L. (L.) major. On another point, combination therapy is a very prom ising alternative to improve the efficacy of the treatments against leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to highlight that each species of Leish mania presents specific biochemical and molecular characteristics, and their sensitivity to drugs is different [25]. Published studies reported the in vivo efficacy of treatments with FEX and ClAlPc against different species that cause leishmaniasis, such as L. donovani, L infantum, L. amazonensis, and L. braziliensis, showing promising results [5][6][7]13,15,26] However, until now, no study has been found that evaluated the effectiveness of thes treatments against L. (L.) major. On another point, combination therapy is a very prom ising alternative to improve the efficacy of the treatments against leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is based on the photoactivation of photosensitizer molecules (PSs), which can generate cytotoxic reactive oxygen species (ROS), such as singlet oxygen ( 1 O 2 ) and free radicals when irradiated by visible light at a specific wavelength. The species can damage cellular organelles causing cell death and tissue destruction irreversibly [ 13 ]. Chloroaluminum phthalocyanine (ClAlPc) is a great PS due to its chemical stability, strong absorption spectrum in the red-light range (670–780 nm), high efficiency in generating ROS, and excellent activity against different Leishmania species after PDT [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation